International students’ satisfaction level towards the mobility programme in UiTM Pahang / Duratul Ain Tholibon … [et al.] - Tholibon, Duratul Ain; Mokhtar, Hamizah; Zulkarnain, Mohd Naqiuddin; Mohd Latib, Farah Wahida; Ismail, Noorul Iqhlima Najwa (Universiti Teknologi MARA, Pahang, 2021)
This study aims to examine the level of students’ satisfaction towards the international mobility programme conducted by UiTM Pahang. This study focuses on 25 respondents who are the international mobility students from Universitas Islam Riau, Indonesia. The international mobility programme is conducted within one month, from 15th of July to 10th of August 2019. The objective of this paper is to get the students’ feedback on the activities conducted throughout the programme. The collected data are analysed quantitatively, using the percentage and mean method. The results of this study show that students’ satisfaction towards the international mobility programme conducted by UiTM Pahang indicates a high level of satisfaction. However, there is a moderate level of satisfaction on some issues, especially regarding the facilities around UiTM Pahang.